2019
DOI: 10.1111/bjh.16335
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected low expression of platelet fibrinogen receptor in patients with chronic myeloproliferative neoplasms: how does it change with aspirin?

Abstract: This study was conducted to evaluate the expression of fibrinogen receptors on platelets of Philadelphia-negative chronic myeloproliferative neoplasm (MPN) patients. We collected blood samples from 40 consecutive MPN patients and healthy volunteers. We performed flow cytometry analysis of P-selectin expression and integrin beta-3, activation of glycoprotein (GP) IIb/IIIa and fibrinogen receptor exposure (PAC-1 binding). Surprisingly, we found a very low PAC-1 binding capacity in MPN patients; however, the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A decrease in PAC-1-binding was also documented by Jensen et al, despite a normal expression of GPIIb/IIIa [22]. Finally, our recent work confirmed a reduced activation of GPIIb/IIIa in MPN patients, with a recovery of the PAC-1-binding capacity after acetylsalicylic acid intake [29]. The most interesting aspect of our experience was the recovery of PFR expression-to levels very close to that of healthy subjects-in patients under prophylaxis with low doses of acetylsalicylic acid.…”
Section: From Platelet Fibrinogen Receptors To Thrombin Generation: the "Circulating Wound" Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…A decrease in PAC-1-binding was also documented by Jensen et al, despite a normal expression of GPIIb/IIIa [22]. Finally, our recent work confirmed a reduced activation of GPIIb/IIIa in MPN patients, with a recovery of the PAC-1-binding capacity after acetylsalicylic acid intake [29]. The most interesting aspect of our experience was the recovery of PFR expression-to levels very close to that of healthy subjects-in patients under prophylaxis with low doses of acetylsalicylic acid.…”
Section: From Platelet Fibrinogen Receptors To Thrombin Generation: the "Circulating Wound" Modelsupporting
confidence: 88%
“…Resistance phenomena are not infrequent, often manifesting themselves with microcirculation disorders, which can be overcome with the administration of low doses twice a day (more effective than doubling the dosage by maintaining a single administration) [ 82 , 83 , 84 ]. In our study on platelet fibrinogen receptor expression in MPNs, by focusing on the group of patients under ASA and with no history of thrombosis, it was found that subjects with persistent microcirculatory disorders show a higher PAC-1-binding capacity if compared to the asymptomatic ones [ 29 ]. As said before, the fibrinolytic and hypoprothrombinemic properties could be more important than the pure antiplatelet properties; for this reason, we have often wondered if ASA is really to be considered the best strategy in MPNs.…”
Section: Current Therapies and Rising Therapeutic Alternativesmentioning
confidence: 99%
“…It should be also mentioned that C1INH promoted the inhibitory effect on thrombin mediated exposure of platelet fibrinogen receptors (PFR) measured by PAC1 binding, this serine protease inhibitor might play a role in pathophysiologic reductions of PFR exposure in the cases of myeloproliferative neoplasms. 38 , 39 Further studies in this area of research may afford new information about the mechanisms of hematologic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of JAK2V617F in platelet function remains unclear. In vitro analysis of platelets isolated from MPN patients suggests there may be defects in signal transduction and integrin activity (Moore et al, 2013;Lucchesi et al, 2020). While in JAK2V617F-positive mouse models, studies have suggested changes in platelet aggregation in vitro (Hobbs et al, 2013) and others identify aberrant hemostasis in vivo, but no clear platelet phenotype (Etheridge et al, 2014;Lamrani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%